Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
3( x + 2) - 2( x + 1) = 26
=> 3x + 6 - 2x - 2 = 26
=> x + 4 = 26
=> x = 26 - 4 = 22
Vậy x = 22
\(=\frac{-1}{14}\)
\(=\frac{1}{14}\)
~~~~~ Chúc bạn học tốt ~~~~~
3(x + 2) - 2(x + 1) = 26
3x + 6 - 2x + 2 = 26
(3x - 2x) + (6 + 2) = 26
x + 8 = 26
x = 26 - 8
x = 18
(x + 1) + (x + 2) + (x + 3) + ... + (x + 26) = 377
=> x + 1 + x + 2 + x + 3 + ... + x + 26 = 377
=> (x + x + x+ ... + x) + (1 + 2 + 3 + ... + 26) = 377
=> 26x + \(\frac{\left(26+1\right).26}{2}\)=377
=> 26x + 351 = 377
=> 26x = 377 - 351
=> 26x = 26
=> x = 1
< = > 26x + 26.27:2 = 377
26x + 351 = 377
26x = 377 - 351 = 26
x = 26 : 26 = 1
-7-2x = 37-(-26)
Suy ra -7-2x=11
Suy ra -2x=11-7
Suy ra -2x=4
Suy ra 2x= -4
Suy ra x = -4 :2 =-2
a.17-(-x(-x(-x)))=16
17+x-x+x=16
17+x=16
x=16-17
x=-1
b.26-|x+19|=-13
|x+19|=26--13
|x+19|=26+13
|x+19|=39
\(\Rightarrow\)\(\orbr{\begin{cases}x+19=39\\x+19=-39\end{cases}}\)
\(\Rightarrow\)\(\orbr{\begin{cases}x=20\\x=-58\end{cases}}\)
3(x+2)-2(x+1)=26
3(x+1)+3-2(x+1)=26
(3-2).(x+1)+3=26
x+1=26-3
x+1=23
x=23-1
x=22
Vậy x=22